2008
DOI: 10.1074/jbc.m802130200
|View full text |Cite
|
Sign up to set email alerts
|

Sulf Loss Influences N-, 2-O-, and 6-O-Sulfation of Multiple Heparan Sulfate Proteoglycans and Modulates Fibroblast Growth Factor Signaling

Abstract: Sulf1 and Sulf2 are two heparan sulfate 6-O-endosulfatases that regulate the activity of multiple growth factors, such as fibroblast growth factor and Wnt, and are essential for mammalian development and survival. In this study, the mammalian Sulfs were functionally characterized using overexpressing cell lines, in vitro enzyme assays, and in vivo Sulf knock-out cell models. Analysis of subcellular Sulf localization revealed significant differences in enzyme secretion and detergent solubility between the human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
139
1
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 129 publications
(148 citation statements)
references
References 49 publications
7
139
1
1
Order By: Relevance
“…Although these sequences are fairly conserved in the zebrafish Sulfs, the additional stretch of sequences in the C-terminal region of HD of Sulf2 and Sulf2a may confer different function, such that it may alter heparin binding affinity or its localisation to the cell surface. Recently, it has been shown that human SULF2 can modify sulfation of the ECM and shed HSPGs consistent with reports of active fulllength enzyme found in the conditioned medium (Lamanna et al, 2008) thus suggesting Sulfs are more mobile than previously anticipated. It would be interesting to address the HD function of zebrafish Sulfs to observe whether this activity is conserved in all vertebrates and if Sulfs can modify 6-O sulfation on neighbouring cells.…”
Section: Expression Profile Of Hs Enzymes In Zebrafishsupporting
confidence: 84%
See 2 more Smart Citations
“…Although these sequences are fairly conserved in the zebrafish Sulfs, the additional stretch of sequences in the C-terminal region of HD of Sulf2 and Sulf2a may confer different function, such that it may alter heparin binding affinity or its localisation to the cell surface. Recently, it has been shown that human SULF2 can modify sulfation of the ECM and shed HSPGs consistent with reports of active fulllength enzyme found in the conditioned medium (Lamanna et al, 2008) thus suggesting Sulfs are more mobile than previously anticipated. It would be interesting to address the HD function of zebrafish Sulfs to observe whether this activity is conserved in all vertebrates and if Sulfs can modify 6-O sulfation on neighbouring cells.…”
Section: Expression Profile Of Hs Enzymes In Zebrafishsupporting
confidence: 84%
“…Since double Sulf knockout mice die shortly after birth, this is a crucial biological process required for normal growth and development (Lamanna et al, 2006(Lamanna et al, , 2008. Therefore, it is not surprising we found most structures to have at least one family member expressed during early embryonic development.…”
Section: Comparison Of Hs Sulf1 Expression From Various Speciesmentioning
confidence: 91%
See 1 more Smart Citation
“…In contrast to this information about post-translational modifications, little has been reported concerning the proteolytic processing of these enzymes. The present study was prompted by the observation of Sulf fragments in Western blots (7,16,24,25), which suggested chain cleavage and the possible existence of a subunit organization. Here, we provide information about the maturation of these enzymes, their subunit organization, and the requirements for their enzymatic and signaling functions.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of these enzymes to modulate the heparin/HSPG interactions of a number of growth factors, morphogens, and chemokines has been confirmed in direct binding assays (9,(11)(12)(13). In some cellular contexts, the Sulfs act to promote signaling pathways (Wnts, bone morphogenetic protein, and glial cell-derived neurotrophic factor) (9 -11, 14), whereas in others the Sulfs are inhibitory (fibroblast growth factor-2 and transforming growth factor-␤) (15)(16)(17). The importance of the Sulfs in development has been revealed by gene knockdown (8) and knock-out studies (11, 18 -20).…”
mentioning
confidence: 99%